Research on the facile regeneration of degraded cathode materials from spent LiNi0.5Co0.2Mn0.3O2 lithium-ion batteries - Yang, Chen; Hao, Yujia; Wang, Jiayi; Zhang, Mingdao; Song, Li; Qu, Jiaan (Frontiers in Chemistry, 2024)
Rational reusing the waste materials in spent batteries play a key role in the sustainable development for the future lithium-ion batteries. In this work, we propose an effective and facile solid-state-calcination strategy for the recycling and regeneration of the cathode materials in spent LiNi0.5Co0.2Mn0.3O2 (NCM523) ternary lithium-ion batteries. By systemic physicochemical characterizations, the stoichiometry, phase purity and elemental composition of the regenerated material were deeply investigated. The electrochemical tests confirm that the material characteristics and performances got recovered after the regeneration process. The optimal material was proved to exhibit the excellent capacity with a discharge capacity of 147.9 mAh g−1 at 1 C and an outstanding capacity retention of 86% after 500 cycles at 1 C, which were comparable to those of commercial NCM materials.